A Case Study on the Restoration of A Historical Masonry Building Based on Field Studies and Laboratory Analyses. Issue 9 (20th October 2020) - Yildizlar, Baris; Sayin, Baris; Akcay, Cemil
ABSTRACT: In historical masonry buildings, the durability of materials used for the structural members can be impaired by climatic conditions and user interventions, and the building may lose its authenticity as a result of functional changes made over time. To restore structures to their original form, the historical changes that have been made over time are researched, and by identifying the original material characteristics it becomes possible to preserve the load-bearing members, thus prolonging their service life. This paper presents a detailed description of the restoration works, which were based on the original geometric and material properties, carried out on a historical masonry building that started out in life as a hospital building in the 1840s, but was later remodeled to become a military prison building and currently serves as the Faculty of Political Sciences of Istanbul University. The study is presented in three stages, namely: i. a research of the historical timeline of alterations of the examined building, ii. a field study, and iii. laboratory analyses. The historical research identifies the structural changes that the building has undergone since its construction, while the field study includes a three-dimensional laser scanning process and the taking of representative samples from different points of the building. In the laboratory stage, the gathered samples are subjected to chemical and mineralogical analyses. The mortar and plaster mixture ratios used in the construction were ascertained through physical and chemical tests to samples taken from the building, and subsequently, all non-original binder materials have been removed and the original mortar-plaster mixture ratios have applied. After a review of the data collected within the scope of this study, it was determined that the two reinforced concrete buildings to the north and south of the site, which were built later in the history of the investigated building, as well as the temporary partition walls to each story, should be removed. Furthermore, it is recommended that the modified facade and interior window forms, together with the blocked-off doorways, should be restored to their original state. The contribution this study makes to literature is based on its focus on a historical masonry building that has lost its original form over time, having been refunctioned for different purposes, that is to be restored back to its original form in terms of its geometric and material properties. The building itself is of particular interest, being the first on the historical peninsula of Istanbul to be constructed using industrial bricks during the Ottoman period. The proposed restoration project can be considered a novel, practical and appropriate approach to authentic restoration.